Implementasi joyful learning melalui deep learning cerita digital untuk meningkatkan minat belajar siswa sekolah dasar - Laksono, Gatot Dwi (Teacher in Educational Research, 2022)
This classroom action research (CAR) aims to: 1) Implement joyful learning through digital storytelling in Grade 1 elementary school, and 2) Analyze the method's impact on students' learning interest. Using Kemmis & McTaggart's CAR model with planning, action, observation, and reflection stages, the study involved 25 first-grade students at SD Negeri Wonoroto The research was conducted through two cycles. The first cycle implemented a 10-minute digital story titled "The Adventures of Kancil" containing basic math concepts (addition), followed by group discussions and interactive quizzes via Quizizz. Quantitative results showed improved learning interest compared to pre-cycle conditions: enthusiasm scores increased from 2.1 to 3.0, participation from 1.8 to 2.7, and media engagement from 2.3 to 3.4. Qualitatively, 65% of students remained focused during the digital story. The second cycle demonstrated more significant improvements: enthusiasm (3.0→3.8), participation (2.7→3.6), and media engagement (3.4→4.0). Qualitatively, 85% of students correctly answered quizzes, indicating enhanced conceptual understanding. Key findings reveal that digital storytelling significantly improved all learning interest indicators: enthusiasm (+0.8 points), active participation (+0.9), media engagement (+0.6), and conceptual understanding (+1.0). The highest improvement in conceptual understanding demonstrates that digital stories not only create joyful learning but also facilitate meaningful deep learning.